2013
DOI: 10.1002/ppul.22877
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor (VDR) polymorphisms and severe RSV bronchiolitis: A systematic review and meta-analysis

Abstract: Available literature supports an association between the FokI polymorphism and severe RSV disease. Determination of VDR receptor polymorphism status could help predict high-risk infants who might benefit from preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 69 publications
2
52
1
1
Order By: Relevance
“…Polymorphisms in SFTPA2 (G223L) and SFTPD (M11T) were shown to be associated with severity of RSV infection in cohorts of patients from Finland and the United States (83, 92, 153). Several studies have also demonstrated a significant association between the FokI start codon polymorphism of the vitamin D receptor gene (VDR) (which codes for an intracellular receptor and transcription factor) and severity of RSV bronchiolitis (68, 80, 102). The FokI polymorphism exacerbates RSV pathogenesis by coding for a VDR that fails to restrain STAT1-mediated antiviral cytokine responses, leading to increased immunopathology (141).…”
Section: Respiratory Syncytial Virusmentioning
confidence: 99%
“…Polymorphisms in SFTPA2 (G223L) and SFTPD (M11T) were shown to be associated with severity of RSV infection in cohorts of patients from Finland and the United States (83, 92, 153). Several studies have also demonstrated a significant association between the FokI start codon polymorphism of the vitamin D receptor gene (VDR) (which codes for an intracellular receptor and transcription factor) and severity of RSV bronchiolitis (68, 80, 102). The FokI polymorphism exacerbates RSV pathogenesis by coding for a VDR that fails to restrain STAT1-mediated antiviral cytokine responses, leading to increased immunopathology (141).…”
Section: Respiratory Syncytial Virusmentioning
confidence: 99%
“…There is also evidence linking vitamin D insufficiency and deficiency to an increased incidence of acute bronchiolitis. A recent systematic review and meta‐analysis concluded that polymorphisms at the VDR level—which might be linked to functional vitamin D deficiency—are usually present in patients hospitalized because of severe RSV bronchiolitis, which is strongly associated with the development of wheezing and asthma later on in life …”
Section: Vitamin D Deficiency and Viral‐induced Exacerbations Of Asthmamentioning
confidence: 99%
“…Genetic factors may also explain the conflicting results on the efficacy of vitamin D (VD), the fat‐soluble‐secosteroid able to potentiate the secretion of type 1 interferon, of chemokines (CXCL8 and CXCL10) and cytokines (TNF‐α and IL‐6) from human BECs, in response to RSV infection . Indeed, in children from South Africa, the Thr1Meth, but not the JUN (c.750G/A) SNP allele of the VD receptor, was identified as a risk factor for severe RSV disease and genotype analysis performed in different populations showed positive relationships between VD receptor FokI (rs2228570) SNP and RSV disease severity . Surfactant protein (SP)‐A and Surfactant protein‐D gene polymorphisms have also been proposed to explain host susceptibility to respiratory disease .…”
Section: Viral and Host Factors That May Downregulate The Innate Antimentioning
confidence: 99%